Interleukin 37 Role in Diabetic Iraqi Patients: A comparison between patients treated with and without Insulin - Mousa, Yousra Yasser; Hussein, Ammar Latif (South Eastern European Journal of Public Health, 2024)
Background: Diabetes Mellitus (DM) is defined as a metabolic disorder that is characterized by some clinical features, such as chronic hyperglycemia accompanied by impairment of carbohydrates metabolism, proteins, and lipids. However, relative or absolute insulin deficiency is associated with the high blood glucose levels, which is attributed to the β-cells dysfunction, insulin resistance or could be both. The anti-inflammatory cytokine interleukin-37 (IL-37) negatively regulates inflammation, therefore, reduces inflammation and alters metabolic pathways. It acts by suppressing inflammatory cytokines and chemokines, activation of IL-37 inhibits inflammation and obstructs the infiltration of pro-inflammatory cells, primarily neutrophils and eosinophils. Aim of Study: The estimation of IL 37 and other biochemical parameters in patients with Diabetes mellitus and study its role in the pathogenicity of the disease. Materials and methods: A case-control study design was adopted to study the relationship between Interleukin 37 and insulin treatment in Nasiriyah in the Diabetes and Endocrinology Specialized Center between December 2023 and January 2024. It was conducted on patients with Diabetes Mellitus type 2 (60 patients) divided into two groups (30 patients treated with Insulin injection) and (30 patient treated with oral tab only). On the other hand, 30 people were taken as a control group without Diabetes Mellitus. Result: Patients with diabetes mellitus have been noticed to have higher levels of IL-37 in comparison to the healthy control groups. In general, patients with diabetes mellitus have higher levels of IL-37 compared to three groups, G1, G2, and healthy control groups. Conclusion We demonstrated that serum levels concentration of IL 1b and IL 37 significantly increased in our patients also FBS, HbA1c, Insulin Resistance, HOMO IR, TG, cholesterol, and decrease C- peptide as compared to healthy individuals.